CORPORATE SOCIAL RESPONSIBILITY, TANGGUNGJAWAB SOSIAL ATAU STRATEGI PERUSAHAAN ? - RATNASARI, RATRI (Jurnal Akuntansi AKUNESA, 2012)
CSR is a form of company’s social responsibility for society around the company as object. Usually, the activities are road maintenance, school structuring, free medical treatment, scholarship and many more. Many companies make CSR activities like a mask that makes the company more “beauty”. Those companies still regard that CSR is just wasting a fund and to secure the company from a society attack.CSR is not only responsibility form of company’s action, however if it’s managed well, CSR can be a company’s strategy which can make profit for the company. Keywords : CSR, Responsibility, Strategy